Family and community medicine workforce training and practice in the Americas. - Puertas Donoso, E. Benjamín; Dias, Bruna Moreno; Clithero-Eridon, Amy R.; Ponzo, Jaqueline; Bouquin, Erin J.; Phillips, Robert L.; Martinez-Bianchi, Viviana; de Valle, Yohana Diaz (Pan American Journal of Public Health / Revista Panamericana de Salud Pública, 2025)
Objective. This study sought to analyze the current state of the training for and practice of family medicine and family and community medicine to identify gaps in these and opportunities to implement strategic actions to strengthen the health workforce. Methods. This paper reports the results of an observational, analytical, cross-sectional study carried out in countries in the World Health Organization's Region of the Americas in 2024. A 22-item survey was administered to members of professional associations of family medicine and family and community medicine practitioners, and a 12-item survey was administered to specialists in this field. Nineteen professional associations and 291 specialists took part in the study. The data were analyzed using descriptive statistics and content analysis. Results. Training in family medicine and family and community medicine is primarily conducted through specialization (68.4%, 13/19) and residency programs (63.2%, 12/19), and a competency exam is required in 63.2% (12/19) of the 23 countries included in the study, represented by 19 professional associations. Training programs cover topics relevant to professional practice, but progress needs to be made, especially in addressing emerging topics. There are few opportunities for continuing education, as reported by 53.7% (29/54) of specialists in Central America, the Latin Caribbean and Mexico, and 35.0% (79/226) in South America. There is a gap in actions aimed at improving working conditions, with policies for well-being and retention implemented in only 36.8% (7/19) of the countries. In addition, responses to open-ended questions indicated that many professionals had a heavy workload, and that their jobs were insecure and precarious, as well as that remuneration was incompatible with their functions, that infrastructure was inadequate, and there was a lack of resources for practice. Despite sampling limitations related to the non-probabilistic design of the study and the unequal participation among countries, it nonetheless provides valuable evidence about training and practice in family and community medicine in the Region of the Americas. Conclusions. Although the practice of family medicine and family and community medicine has been established for more than three decades in the Region, the field faces significant implementation challenges. Strategic investments are needed to strengthen the recognition and perceived value of family and community medicine as a specialty, ensure adequate working conditions and improve the quality of education. Strengthening family and community medicine by undertaking coordinated actions across multiple stakeholders is crucial for building resilient health systems grounded in primary health care.